Chemical analysis and nutritional assessment of artocarpus heterophyllus lam. (jack fruit) defatted seeds used as addictive in feed for clarias gariepinus post juveniles (2013)
A 49-day feeding trial was carried out with feeds supplemented with microgram quantities of the defatted seeds of Artocarpus heterophyllus in the diets of Clarias gariepinus at the post juveinile stage. Five diets at 40% crude protein were formulated containing 0, 15, 30, 45 and 60x106 μg DAH seed as additive. Each dietary treatment was replicated three times with 10 fish per replicate. Proximate composition of the defatted seed showed that it was rich in protein, carbohydrate and minerals. Fish on DAH–supplementd diets had better survival rates than the control. Haematology, plasma biochemistry and gross tissue examination were also carried out. No significant differences (p<0.05) were observed between the fish on DAH-containing treatments and the control. There might be need to further process and test defatted A. heterophyllus seeds as either probiotic or prebiotic on young fish for longer periods in order to take advantage of its rich supply of nutrients